Entire X-band region metamaterial absorber and reflector with a microstrip patch switch for X-band applications - M.M. Gajibo; M. K. A. Rahim; N. A. Murad; O. Ayop; H.A. Majid; M. Aminu-Baba; R. Dewan (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A metamaterial structure capable of operating as a wide band absorber as well as an AMC reflector is presented in this report. A microstrip patch copper was used as a switch to switch between the two modes. An FR4 substrate was used and the incidental wave angles were varied from 00 to 600. Simulations results showed that the absorber was able achieve 96% absorption at 13.05 GHz and 100% absorption at 10.00 GHz and 12.00 GHz. Furthermore, it archived over 85% absorption for the entire X-band frequency range. The AMC reflector also was able to achieve 84.97%, 82.88% and 78.69% for incident angles 00, 200 and 400 respectively. Unfortunately, the structure is polarization sensitive.